Probing the nature of the G1 clump stellar overdensity in the outskirts of M31 - Faria, D; Johnson, R; Ferguson, AMN; Irwin, M; Ibata, R; Johnston, K; Lewis, G; Tanvir, N (2007)
We present deep Hubble Space Telescope ACS observations of the G1 clump, a distinct stellar overdensity lying at ∼30 kpc along the southwestern major axis of M31, close to the G1 globular cluster (from the work of Ferguson and coworkers). Our well-populated color-magnitude diagram reaches ∼7 mag below the red giant branch tip with 90% completeness, and allows the detection of various morphological features that can be used to derive detailed constraints on the age and metallicity of the constituent stellar population. We find that the color-magnitude diagram is best described by a population with a large age range (≥ 10 Gyr) and a relatively high mean metallicity [M/H] = -0.4. The spread in metallicity is constrained to be ≤0.5 dex. The star formation rate in this region has declined over time, with the bulk of the stellar mass having formed >6 Gyr ago. Nonetheless, a nonnegligible mass fraction (≈10%) of the population has formed in the last 2 Gyr. We discuss the nature of the G1 clump in light of these new stellar population constraints and argue that the combination of stellar content and physical size make it unlikely that the structure is the remnant of an accreted dwarf galaxy. Instead, the strong similarity between the stellar content of the Gl clump and that of the M31 outer disk suggests that the substructure is a fragment of the outer disk, perhaps torn off from the main body during a past accretion/merger event; this interpretation is consistent with extant kinematical data. If this interpretation is correct, our analysis of the stellar content provides further evidence that the outskirts of large disk galaxies have been in place for a significant time. © 2007. The American Astronomical Society. All rights reserved.